Typical Responses in Giving Evaluation: An Analysis of High and Low Context Culture Communication - Ferany Arifin; Fikriasih Wigati; Zubaedah Lestari (Master Program in Linguistics, Diponegoro University, 2013)
This paper aims at discussing high and low context in responses given by the students to evaluate their friend’s impromptu speech performance. The study focuses on the characteristics of high and low context represented specifically on (1) direct-indirect (2) simple-complex response, and (3) relationship orientation. The study is based on the analysis of ten responses given by ten students with different sexes. Classroom observation followed by transcription analysis is used. The data were collected naturally at undergraduate campus. The result shows that using indirect and complex responses can maintain harmonious relationship with others. The basic asumption is that the students tend to communicate in high level context. Penelitian ini bertujuan untuk membahas konteks tinggi dan rendah dalam mengevaluasi performansi pidato tanpa persiapan temannya. Penelitian ini memusatkan perhatian pada ciri konteks tinggi dan rendah yang direpresentasikan oleh (1) tanggapan langsung-tak langsung (2) sederhana-kompleks, dan (3) orientasi hubungan. Penelitian ini didasarkan pada sepuluh tanggapan yang diberikan oleh sepuluh mahasiswa pria dan wanita. Pengamatan kelas yang diikuti dengan analisis transkripsi digunakan untuk pengumpulan data. Data dikumpulkan di kampus diploma. Analisis menunjukkan bahwa siswa cenderung menggunakan tanggapan kompleks dan tak langsung agar dapat menjaga keharmonisan hubungan dengan temannya. Oleh karena itu asumsi dasarnya adalah bahwa siswa cenderung berkomunikasi dalam konteks level tinggi.